Effects of creatine monohydrate on finishing pig growth performance, carcass characteristics, and meat quality - James, B.W.; O’Quinn, P.R.; Andrews, B.S.; Goodband, Robert D.; Unruh, John A.; Tokach, Michael D.; Nelssen, Jim L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Growth performance, carcass characteristics, and meat quality were evaluated from 320 pigs fed either a control diet or diets containing added creatine monohydrate (CMH). Dietary treatments, initiated 30-d prior to slaughter (192 lb BW), consisted of: 1) a control diet; 2) control diet with 3 g CMH/pig/d for 30 d (maintenance); 3) 25 g CMH/pig/d for 5 d followed by 3 g CMH/pig/d for the next 25 d (early load); 4) or 25 g CMH/pig/d 5 d before slaughter (late load). The results from this experiment suggest that added CMH does not affect finishing pig growth performance but may increase longissimus muscle firmness and decrease drip loss at 14 d postmortem.
Keywords: Swine; Creatine monohydrate; Carcass characteristics; Meat quality